Influence of lipid concentration on encapsulation and particle size in the development of liposomal irinotecan - A. V. Stadnichenko; Y. M. Krasnopolsky; T. G. Yarnykh (Zaporozhye State Medical University, 2017)
Purpose. For creation of liposomal irinotecan form, the influence of lipid concentration on the encapsulation of the active substance and nanoparticle size was necessary to investigate. Materials and methods. We used «chemical gradient" method for liposomes formulation, in the variety of "pH gradient". Ammonium citrate at pH 2.5 was used as internal buffer. Lipid film was obtained, by evaporation technics with further high pressure homogenization with Microfluidics Microfluidizer M-110P apparatus. "Chemical gradient" was created by ultrafiltration, with "Minim 2" apparatus. Ultrafiltration cartridge with an upper cut-off 30 kDa was used. Encapsulation was measured using HPLC methods developed in variant of gel chromatography, with Shimadzu LC-20 instrument. The particle size was measured by laser diffraction method withe "Zetasizer Nano ZS" instrument. Results. For the preparation of liposomes was applied a constant lipid ratio with varying of total lipid concentration. The ratio of lipids in the experiment was a phosphatidylcholine / cholesterol 80/20 % by weight. A total concentration was investigated in range from 10 mg/ml to 30 mg/ml. The number of extrusion cycles consisted from 3 cycles at 1500 bar, in case of 10 mg/ml concentration, to 17 cycles at 1500 bar, in case of 30 mg/ml concentration. Conclusions. It was shown that the lipid concentration from 25 mg/ml led to particles formation with size more than 5000 nm, and it was not possible to reduce them by high pressure homogenization method. It was proven that the most optimal, in terms of technology and the final characteristics of liposomes, was lipids in concentration 20 mg/ml. The degree of encapsulation in this case was 82 ± 0.98 %. The size of the liposomes was 106 nm, 5000 nm particles were absent.